A case of a chlorine inhalation injury in an Ebola treatment unit. Issue 3 (15th October 2015) - Carpenter, Adrian; Cox, A T; Marion, D; Phillips, A; Ewington, I
Abstract : We present a 26-year-old male British military nurse, deployed to Sierra Leone to treat patients with Ebola virus disease at the military-run Kerry Town Ebola Treatment Unit. Following exposure to chlorine gas during routine maintenance procedures, the patient had an episode of respiratory distress and briefly lost consciousness after exiting the facility. Diagnoses of reactive airways disease, secondary to the chlorine exposure and a hypocapnic syncopal episode were made. The patient was resuscitated with minimal intervention and complete recovery occurred in less than 1 week. This case highlights the issues of using high-strength chlorine solution to disinfect the red zone. Although this patient had a good outcome, this was fortunate. Ensuring Ebola treatment centres are optimally designed and that appropriate management systems are formulated with extraction scenarios rehearsed are important to mitigate the chlorine-associated risk.